2018
DOI: 10.1111/bph.14428
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐351‐5p aggravates intestinal ischaemia/reperfusion injury through the targeting of MAPK13 and Sirtuin‐6

Abstract: Our data showed that miR-351-5p aggravated II/R injury by promoting intestinal mucosal oxidative stress, inflammation and apoptosis by targeting MAPK13 and sirtuin-6.These data provide new insights into the mechanisms regulating II/R injury, and of miR-351-5p could be considered as a novel therapeutic target for such injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Previous studies have shown that miRNAs can control the pathological process of II/R injury (Y. Hu et al, ; Z. Li et al, ; Y. Li, Wen, et al, ; Y. Li, Xu, et al, ). In addition, some miRNAs including miR‐375 and miR‐371 have been confirmed as the markers for clinical diagnosis and treatment of diseases (Piano et al, ; Salvatori et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that miRNAs can control the pathological process of II/R injury (Y. Hu et al, ; Z. Li et al, ; Y. Li, Wen, et al, ; Y. Li, Xu, et al, ). In addition, some miRNAs including miR‐375 and miR‐371 have been confirmed as the markers for clinical diagnosis and treatment of diseases (Piano et al, ; Salvatori et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are important endogenous regulators leading to RNA degradation and/or inhibition of protein synthesis (He et al, ; Y. Hu et al, ; Z. Liu et al, ). Recent studies have shown that some miRNAs including miR‐378, miR‐351‐5P, and miR‐665‐3p play important roles in regulating II/R injury (Y. Hu et al, ; Z. Li et al, ; Y. Li, Wen, et al, ; Y. Li, Xu, et al, ). MiR‐378 can protect against II/R injury via inhibiting intestinal mucosal cell apoptosis (Y. Li, Wen, et al, ; Y. Li, Xu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations